The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.jmedchem.2c00173
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the Dark: Highly Selective Inhibition of Serine/Threonine Kinase 17A with Pyrazolo[1,5-a]pyrimidine-Based Macrocycles

Abstract: Serine/threonine kinase 17A (death-associated protein kinase-related apoptosis-inducing protein kinase 1DRAK1) is a part of the death-associated protein kinase (DAPK) family and belongs to the so-called dark kinome. Thus, the current state of knowledge of the cellular function of DRAK1 and its involvement in pathophysiological processes is very limited. Recently, DRAK1 has been implicated in tumorigenesis of glioblastoma multiforme (GBM) and other cancers, but no selective inhibitors of DRAK1 are available ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
(142 reference statements)
0
23
0
Order By: Relevance
“…In contrast to DRAK2, DRAK1 gets less attention. Recently, Kurz et al identified a macrocyclic scaffold based on the multifunctional pharmacophore pyrazole­[1,5- a ]­pyrimidine to obtain the highly selective CK2 inhibitor IC19 ( 24 , Figure A) and then identified a lead structure ( 25 , Figure A) of a selective DRAK1 inhibitor based on the optimization of IC19 by modifying the back-pocket interaction (IC 50 = 155 nM) . The surface of the cocrystal structure of compound 25 and DRAK1 reveals a large unoccupied back pocket at which the benzylic portion of 25 is pointing (PDB code 7QUE).…”
Section: Small-molecule Inhibitors Of Dapksmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to DRAK2, DRAK1 gets less attention. Recently, Kurz et al identified a macrocyclic scaffold based on the multifunctional pharmacophore pyrazole­[1,5- a ]­pyrimidine to obtain the highly selective CK2 inhibitor IC19 ( 24 , Figure A) and then identified a lead structure ( 25 , Figure A) of a selective DRAK1 inhibitor based on the optimization of IC19 by modifying the back-pocket interaction (IC 50 = 155 nM) . The surface of the cocrystal structure of compound 25 and DRAK1 reveals a large unoccupied back pocket at which the benzylic portion of 25 is pointing (PDB code 7QUE).…”
Section: Small-molecule Inhibitors Of Dapksmentioning
confidence: 99%
“…Based on this information, the role of the back pocket was further explored, and a series of macrocyclic compounds were synthesized. Structural optimization of the compounds resulted in IC 50 values of 31, 15, and 49 nM for compound 26 (Figure A) substituted with 1-phenylethanamides, CK228 ( 27 , Figure A) generated from 1-(pyridin-4-yl)­ethanamines ( S -conformation) by an amide coupling reaction, and CK156 ( 28 , Figure A) with the introduction of a 2-methylpropan-2-amine, respectively . The cocrystal structure of 28 with DRAK1 shows that the tert -butyl residue of 28 points to the back pocket of DRAK1 (PDB code 7QUF), forming a conserved hydrogen bond with the hinge region and Lys90.…”
Section: Small-molecule Inhibitors Of Dapksmentioning
confidence: 99%
See 1 more Smart Citation
“…38). 136 Recently, Kurz et al 137 have synthesized pyrazolopyrimidine-based macrocyclic skeletons and investigated their selectivity of inhibition for serine/ threonine kinase 17A.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…The second part of the talk focused on studies showcasing the development of macrocyclic kinase inhibitors. Hanke and colleagues successfully employed a macrocyclization approach in the design of inhibitors targeting the casein kinase 2 (CK2) [58] and but also to generate potent and selective inhibitors for understudied protein kinases such as STK17‐A and ‐B [59] . Moreover, this strategy was used to generate promising inhibitors targeting the epidermal growth factor receptor kinase (EGFR) with activating exon 19 deletions (EGFR‐Del19).…”
Section: Macrocyclesmentioning
confidence: 99%